Person reference and gender (non-)Binarity: A quantitative survey of the front pages of Czech periodicals - Vít Kolek (Gender a Výzkum, 2023)
Criticising the use of the generic masculine, feminist and gender linguists have proposed different alternatives. In the Czech context, the following three types of alternatives can be distinguished: (1) feminisation, (2) neutralisation and paraphrases, and (3) making non-binary persons linguistically more visible. Empirical studies on the usage frequency of these alternatives, however, are lacking. This paper addresses this issue by analysing agentive nouns and the feminisation of surnames in selected Czech newspapers. The results show that in references to individual women almost exclusive use is made of feminine expressions. Mixed-gender groups are still largely referred to using the generic masculine. In only a minority of occurrences are neutralising strategies used to refer to persons. What is more common, however, is to find neutralising strategies being used where the intention of expressing gender fairness was probably not the reason for their use, as referring to persons is not their primary function. Neither pair forms nor graphic symbols for non-binary reference are used. The surnames of female foreign nationals are almost always feminised, even though this is not necessary and the texts provide other linguistic means of identifying the persons as women. Based on an analysis of the distribution of generically-intended masculine expressions in the analysed texts, I propose dividing them into two types according to whether or not there is an obvious inclusion of females and non-binary persons.